Pemberdayaan UMKM melalui Digital Marketing di Desa Tenggulun Kecamatan Solokuro Kabupaten Lamongan - Afan Zaini, Ahmad; Zawawi, Abdullah; Auwalia, Atik Fitrotul; lisnawati, Ika; Annisa’ Nur Aini, Sukma Fajar; Farih fakhruddin, Muhammad Zaidan (Fakultas Ekonomi dan Bisnis Islam Institut Pesantren Sunan Drajat Lamongan, 2023)
Aware of the potential possessed by Micro, Small, and Medium Enterprises (MSMEs) in Tenggulun Village, it is essential to develop these potentials or assets. Furthermore, MSMEs play a vital role in local economic growth, and the application of digital technology can be the key to their success in expanding their businesses. Empowerment through Digital Marketing is undertaken to enhance the potential for reaching a broader and more optimal market. This assistance is manifested in the form of empowerment, with the primary target being the MSME entrepreneurs themselves, thus maximizing the potential of each MSME. This ki employs the Participatory Action Research (PAR) method, with interviews and community engagement as data collection techniques. The research findings indicate that MSMEs in Tenggulun Village face challenges in marketing their products to a wider audience, both on social media and websites, which could improve their brand image and boost sales of their products or services. Therefore, efforts are required to provide training and mentoring to MSMEs in understanding and effectively implementing digital marketing strategies.